Efeitos do captopril e do enalapril sobre a resposta imune humoral e celular - Arruda, Liziane Cristina de Almeida (2016)
The angiotensin-converting-enzyme (ACE) inhibitors act not only in the treatment of hypertension and in cardiovascular diseases but also have immunomodulatory properties. The objective of this study was to determine the effect of captopril and enalapril on humoral and cellular immune responses in mice C57BL6. In the present work, we have investigated the effect of enalapril on ovalbumin-specific IgG1 and IgG2c production in mice immunized with EndoFit ovalbumin in the presence of Alhydrogel, as adjuvant. Additionally, we investigated the effect of captopril and enalapril on the frequency, absolute number, and activation of T lymphocytes and B and natural killer (NK) cells in vivo using flow cytometry. The results showed that enalapril significantly increases anti-OVA serum IgG2c in the secondary response without affecting IgG1 synthesis. Moreover, captopril, unlike enalapril, increased the frequency, absolute number, and activation of the CD4+ lymphocyte subpopulation. Thus, these data expand our understanding on the properties of enalapril on the immune response.